Epidemiology and genetic diversity of human respiratory syncytial virus in Belgium between 2011 and 2019 - Kaat Ramaekers; Els Keyaerts; Lieselot Houspie; Kurt Beuselinck; Marijke Reynders; Katrien Lagrou; Marc Van Ranst; Annabel Rector (Virology Journal)
Abstract Background Human respiratory syncytial virus (HRSV) is worldwide one of the leading causes of acute respiratory tract infections in young children and the elderly population. Two distinct subtypes of HRSV (A and B) and a multitude of genotypes have been described. The laboratory of Clinical and Epidemiological Virology (KU Leuven/University Hospitals Leuven) has a long-standing history of HRSV surveillance in Belgium. Methods In this study, the seasonal circulation of HRSV in Belgium was monitored during 8 consecutive seasons prior to the SARS-CoV-2 pandemic (2011–2012 until 2018–2019). By use of a multiplex quantitative real time PCR panel, 27,386 respiratory samples were tested for HRSV. Further subtyping and sequencing of the HRSV positive samples was performed by PCR and Sanger sequencing. The prevalence and positivity rate were estimated in 4 distinct age groups and the circulating strains of each subtype were situated in a global context and in reference to the described genotypes in literature. Results HRSV circulated in Belgium in a yearly re-occurring pattern during the winter months and both HRSV subtypes co-circulated simultaneously. All HRSV-B strains contained the 60 nt duplication in the HVR2 region of the G gene. Strains of subtype HRSV-A with a 72 nt duplication in the HVR2 region were first observed during the 2011–2012 season and replaced all other circulating strains from 2014 to 2015 onwards.